Comparative performance of a genetically-encoded voltage indicator and a blue voltage sensitive dye for large scale cortical voltage imaging - Mutoh, Hiroki; Mishina, Yukiko; Gallero-Salas, Yasir; Knöpfel, Thomas (Frontiers in Cellular Neuroscience, 2015)
Traditional small molecule voltage sensitive dye indicators have been a powerful tool for monitoring large scale dynamics of neuronal activities but have several limitations including the lack of cell class specific targeting, invasiveness and difficulties in conducting longitudinal studies. Recent advances in the development of genetically-encoded voltage indicators have successfully overcome these limitations. Genetically-encoded voltage indicators (GEVIs) provide sufficient sensitivity to map cortical representations of sensory information and spontaneous network activities across cortical areas and different brain states. In this study, we directly compared the performance of a prototypic GEVI, VSFP2.3, with that of a widely used small molecule voltage sensitive dye (VSD), RH1691, in terms of their ability to resolve mesoscopic scale cortical population responses. We used three synchronized CCD cameras to simultaneously record the dual emission ratiometric fluorescence signal from VSFP2.3 and RH1691 fluorescence. The results show that VSFP2.3 offers more stable and less invasive recording conditions, while the signal-to-noise level and the response dynamics to sensory inputs are comparable to RH1691 recordings.